Optimization of cloud point extraction and solid phase extraction methods for speciation of arsenic in natural water using multivariate technique - Baig, Jameel A.; Kazi, Tasneem G.; Shah, Abdul Q.; Arain, Mohammad B.; Afridi, Hassan I.; Kandhro, Ghulam A.; Khan, Sumaira (Analytica chimica acta)
The simple and rapid pre-concentration techniques viz. cloud point extraction (CPE) and solid phase extraction (SPE) were applied for the determination of As 3+ and total inorganic arsenic (iAs) in surface and ground water samples. The As 3+ was formed complex with ammonium pyrrolidinedithiocarbamate (APDC) and extracted by surfactant-rich phases in the non-ionic surfactant Triton X-114, after centrifugation the surfactant-rich phase was diluted with 0.1 mol L −1 HNO 3 in methanol. While total iAs in water samples was adsorbed on titanium dioxide (TiO 2); after centrifugation, the solid phase was prepared to be slurry for determination. The extracted As species were determined by electrothermal atomic absorption spectrometry. The multivariate strategy was applied to estimate the optimum values of experimental factors for the recovery of As 3+ and total iAs by CPE and SPE. The standard addition method was used to validate the optimized methods. The obtained result showed sufficient recoveries for As 3+ and iAs (>98.0%). The concentration factor in both cases was found to be 40.